Identidad cultural del idioma wayúunaiki en una Institución Educativa del municipio de Uribía, La Guajira - Katherin Daviannis, Palmar Barliza (Universidad Antonio Nariño, 2021)
In recent years the issue of cultural identity has gained great importance in the field of education, in this case, Wayúunaiki as a mother tongue is an element that is part of the identity of this culture, that is why. The objective of the present study was to compare the differences in the transmission and development of the use of the Wayúunaiki language within the classroom of the Normal Superior Indigenous educational institution and the Alfonso López Pumarejo educational institution of the municipality of Uribia in the department of Guajira. The research had a descriptive scope and within the main findings it was possible to determine that a large part of these children are people who demonstrate their Wayúunaiki language, because it is observed that 50% of children and young people still retain the essence of speech, which which is reflected in daily life, in games, spaces shared with family, friends, daily conversations, despite interacting and knowing the western world, maintains the essence of the Wayúunaiki language, but which are not reinforced within the nucleus family. Likewise, based on these results, the author made some recommendations that would serve to reinforce the cultural identity of children within educational institutions